Swedish naturalist Peter Artedi (1705–1735) and his place in the history of biosystematics as exemplified by his Ichthyologia sive opera omnia piscibus of 1738 - Pietsch, Theodore W.; Aili, Hans (Zootaxa, 2022)
An English translation of the Swedish naturalist Peter Artedi’s great masterpiece Ichthyologia sive opera omnia piscibus (1738) has allowed for an increased understanding of the importance of his work to ichthyology and to the history of biosystematics in general. The opportunity to study Ichthyologia in English for the first time emphasizes like never before Artedi’s thoroughly modern approach. His description of the European Perch, Perca fluviatilis Linnaeus, 1758, is provided as an example of the extent to which he applied his methodology to a specific taxon.